The Scientific Centers of Iran during the Ilkhanid Period - Parvin-e Torkamani-ye Azar (تاریخ اسلام, 2007)
The Mongol’s lack of endorsement of a particular religion caused the growth and spread of a great number of ideological, intellectual and cultural groups in Iran. This in turn brought about a kind freedom and equality in education and study for the followers of all religions and religious creeds causing a large number of scholars and scientists to gather in the schools and scientific centers of big cities in this period. Important schools and scientific centers of this period include: Maragheh Observatory; The Center for the Education and Research of Mathematics and Astronomy; Shanb-e Ghazan Complex; The Center for the Teaching and Learning of Religious Knowledge (Hanafi and Shafi‘i); Rab‘-e Rashidi which offered education from the elementary to college levels and which in addition to religious sciences (Hanafi and Shafi‘i), was also dedicated to the education of medicine as well; Soltaniyyeh School which was dedicated to the teachings of the Ithna-‘Ashari (Twelver) Shi‘ah creed; and the Mobil School, an innovative Iranian educational center that was created to meet the educational needs of nomadic life. Each one of these educational centers offered educational and welfare services on the sidelines of their main activities such as an educational center for orphans, khanghah (house of Sufi activities), dar us-siyadat, dar ush-shifa’ (hospital), library and a publishing house as well.